Hypertensive disorders of pregnancy and emotional and behavioural problems in children: a longitudinal population-based study. - Dachew, Berihun Assefa; Scott, James G.; Mamun, Abdullah; Alati, Rosa (European Child & Adolescent Psychiatry, 2020)
There is evidence that offspring of mothers who have hypertensive disorders of pregnancy (HDP) are at increased risk of adverse health outcomes. This study aims to examine the association between maternal HDP and emotional- and behavioural problems in offspring at age 11 years as reported by teachers and parents. The current study is based on the Avon Longitudinal Study of Parents and Children (ALSPAC), a prospective, population-based study that has followed a cohort of offspring since their mothers were pregnant. Childhood emotional- and behavioural problems were measured using the Strengths and Difficulties Questionnaire (SDQ), completed by parents (n = 7196) and the child's teacher (n = 7411). Maternal preeclampsia, but not gestational hypertension, was associated with teacher-reported total behavioural difficulties (RR = 1.62; 95% CI 1.03–2.52) and internalising problems in children [peer problems (RR = 1.48; 95% CI 1.06–2.08) and emotional problems (RR = 1.68; 95% CI 1.13–2.51)]. No associations between preeclampsia and/or gestational hypertension and parent-reported emotional- and behaviour problems were observed. Our study showed that children exposed to preeclampsia had higher risk of teacher-reported total behavioural difficulties and internalising problems compared with unexposed children. The findings suggest emotional- and behavioural difficulties may not be evident in all settings, hence the importance of collecting evidence from multiple informants.